The importance of engaging students on public assistance: New insights and recommendations for practice. Issue 3 (October 2019) - Elias, Nicole M; Marrin, Madeleine
Student engagement in institutions of higher education has become a central priority for educators and administrators. What "student engagement" means for a diverse student body is an important question for public institutions with justice-related missions. As social welfare policy shifts to allow more recipients of public assistance access to higher education, research regarding their engagement experiences remains scarce. To support a socioeconomically diverse student body, consistent with the Network of Schools of Public Policy, Affairs, and Administration (NASPAA) standards, this project explores the nature of engagement among student recipients of public assistance by asking the following research questions: what forms of engagement with students on public assistance take place? Why is engaging students on public assistance important? How can we foster greater engagement with students on public assistance? To answer these questions, student and faculty focus groups are conducted. From this analysis, we highlight normative implications of engaging a socioeconomically diverse student population and present recommendations for fostering greater engagement.